Beyond allostatic load: Rethinking the role of stress in regulating human development. (26th November 2013) - Ellis, Bruce J.; Del Giudice, Marco
Abstract How do exposures to stress affect biobehavioral development and, through it, psychiatric and biomedical disorder? In the health sciences, the allostatic load model provides a widely accepted answer to this question: stress responses, while essential for survival, have negative long-term effects that promote illness. Thus, the benefits of mounting repeated biological responses to threat are traded off against costs to mental and physical health. The adaptive calibration model, an evolutionary–developmental theory of stress–health relations, extends this logic by conceptualizing these trade-offs as decision nodes in allocation of resources. Each decision node influences the next in a chain of resource allocations that become instantiated in the regulatory parameters of stress response systems. Over development, these parameters filter and embed information about key dimensions of environmental stress and support, mediating the organism's openness to environmental inputs, and function to regulate life history strategies to match those dimensions. Drawing on the adaptive calibration model, we propose that consideration of biological fitness trade-offs, as delineated by life history theory, is needed to more fully explain the complex relations between developmental exposures to stress, stress responsivity, behavioral strategies, and health. We conclude that the adaptive calibration model and allostatic load model are only partially complementary and, in some cases, support different approaches to intervention. In the long run, the field may be better served by a model informed by life history theory that addresses the adaptive role of stress response systems in regulating alternative developmental pathways.